Chemical Composition and Nutritional Categorization of Fish Meals Produced and Marketed in Senegal for Animal Feeding - Ayssiwede, S.B.; Mouanda, V.C.; Issa, Y.A.; Djettin, A.E.; Hane, M.B.; Missohou, A. (Pakistan Journal of Nutrition, 2016)
We assessed the chemical and nutritional compositions of 154 fish meal samples produced and marketed in Senegal. The fish meal samples (93 from 4 artisanal and 61 from 3 industrial units) were collected, stored and analyzed in the Laboratory of Nutrition and Animal Feeding (LANA) of EISMV-Dakar from September 2012 to July 2013. The results showed that the fish meals produced in Senegal were all fatty, regardless of whether they were artisanal or industrial. Overall, they showed significant variation (p